2016
DOI: 10.1515/helmin-2016-0017
|View full text |Cite
|
Sign up to set email alerts
|

Application of multiplex PCR for the simultaneous detection of Taenia spp. from domestic dogs in the north of Iran

Abstract: SummaryThe family Taeniidae is of great importance in the medical and veterinary fi elds, particularly in the tropics and subtropics. Identifi cation of eggs of different Taenia spp. in the fi nal host by morphological examination is diffi cult owing to their similarity. Therefore, a multiplex polymerase chain reaction (PCR) targeting a mitochondrial gene was applied to identify morphologically indistinguishable eggs. Fecal samples from 100 domestic dogs, from the Mazandaran province in Iran, were examined usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
(25 reference statements)
1
4
0
Order By: Relevance
“…In this study, no 395 bp amplicon, representative of E. multilocularis eggs, was observed in the Taeniid-positive fecal samples of dogs. Our result is in line with a couple of studies performed in north of Iran, in which no E. multilocularis was detected in dog fecal samples [ 16 , 25 ]. Studies have shown that median estimate of the total numbers of AE cases in the world is 18,235 per year [ 34 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In this study, no 395 bp amplicon, representative of E. multilocularis eggs, was observed in the Taeniid-positive fecal samples of dogs. Our result is in line with a couple of studies performed in north of Iran, in which no E. multilocularis was detected in dog fecal samples [ 16 , 25 ]. Studies have shown that median estimate of the total numbers of AE cases in the world is 18,235 per year [ 34 ].…”
Section: Discussionsupporting
confidence: 93%
“…Among parasites detected by flotation method, Taeniid eggs were observed in 5.6 % samples which was less than the infection rate reported by Rahimi et al . [ 16 ] in Mazandaran, north of Iran. The cestode family of Taeniidae contains 2 genera, Taenia and Echinococcus , which are closely related to each other, and their zoonotic importance made them the subject of intensive epidemiological studies [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CE is an emerging neglected disease and a public health concern in the Middle East that results in substantial economic losses [40,41]. Molecular surveys are considered to be the gold standard for the differential diagnosis of human echinococcosis.…”
Section: Discussionmentioning
confidence: 99%